2013
DOI: 10.1089/gtmb.2012.0247
|View full text |Cite
|
Sign up to set email alerts
|

Why Do People Choose Not to Have Screening for Hemochromatosis?

Abstract: The nonattender data presented here indicate that concerns about insurance, anxiety, and use of genetic information are not major factors for why people did not attend workplace information and screening sessions for hereditary hemochromatosis. Practical barriers were the major reasons identified. This highlights that when implementing screening programs, as many practical barriers as possible need to be overcome, so that a maximum number of people who would like to be informed about screening are given the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…However recent studies have shown that there are minimal psychological effects of screening [146][147][148][149]. Additionally, studies outside the United States where insurance and health care access and coverage are less of a concern have suggested that practical reasons such as lack of awareness and access to screening programs are the major reasons for non-participation in screening programs [150]. We believe that screening persons of Northern European descent may be useful; with phenotypic screening with TS preferred over HFE genotyping although TS screening does have limitations due to the performance characteristics of this test [64,151].…”
Section: Screening and Evaluation Of Family Membersmentioning
confidence: 99%
“…However recent studies have shown that there are minimal psychological effects of screening [146][147][148][149]. Additionally, studies outside the United States where insurance and health care access and coverage are less of a concern have suggested that practical reasons such as lack of awareness and access to screening programs are the major reasons for non-participation in screening programs [150]. We believe that screening persons of Northern European descent may be useful; with phenotypic screening with TS preferred over HFE genotyping although TS screening does have limitations due to the performance characteristics of this test [64,151].…”
Section: Screening and Evaluation Of Family Membersmentioning
confidence: 99%